2013
DOI: 10.1051/0004-6361/201221006
|View full text |Cite
|
Sign up to set email alerts
|

The Canada-France High-zQuasar Survey: 1.2 mm observations

Abstract: We report 250 GHz (1.2 mm) observations of a sample of 20 quasars at redshifts 5.8 < z < 6.5 from the Canada-France High-z Quasar Survey (CFHQS), using the Max-Planck-Millimeter-Bolometer (MAMBO) array at the 30-metre telescope of the Institut de Radioastronomie Millmétrique (IRAM). An rms sensitivity of 0.6 mJy was achieved for 65% of the sample, and of 1.0 mJy for 90%. Only one quasar, CFHQS J142952+544717, was robustly detected with S 250 GHz = 3.46 ± 0.52 mJy. This indicates that one of the most powerful k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…Due to atmospheric absorption, this waveband is however difficult to access from the ground, and this has limited studies to relatively small samples of several tens of objects (Omont et al 2001(Omont et al , 2013Isaak et al 2002;Priddey et al 2003;Beelen et al 2006;Wang et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to atmospheric absorption, this waveband is however difficult to access from the ground, and this has limited studies to relatively small samples of several tens of objects (Omont et al 2001(Omont et al , 2013Isaak et al 2002;Priddey et al 2003;Beelen et al 2006;Wang et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, galaxy formation models must evoke strong feedback from active galactic nucleus (AGN) to explain the observed properties of massive galaxies and to avoid the overcooling catastrophe (Croton et al 2006;Bower et al 2006;McNamara & Nulsen 2007;Somerville et al 2008;Fabian 2012;Blanchard et al 1992) Quasar environments give us a look at these powerful engines, and millimeter/submillimeter observations can offer a particularly revealing view of their effects: at these frequencies it is possible to study the cooler dust emission associated with star formation in the host, look for synchrotron emission from energetic particles, and, perhaps most pertinently, to measure energy feedback through observation of the thermal Sunyaev-Zeldovich (tSZ, Sunyaev & Zeldovich 1970, 1972 effect, a direct probe of the thermal energy contained in surrounding gas. Samples observed in this waveband with large ground-based facilities typically consist of, at most, several tens of objects (Omont et al 2001(Omont et al , 2003(Omont et al , 2013Isaak et al 2002;Priddey et al 2003;Beelen et al 2006;Wang et al 2007). Operating at these same frequencies, cosmic microwave background (CMB) surveys cover large sky areas and present the opportunity of studying much larger samples, albeit with much less detail of individual objects.…”
Section: Introductionmentioning
confidence: 99%
“…The (sub-)mm searches have also been performed by targeting more than 60 optically selected QSOs at z ∼ 6, once more favoring quite powerful sources, though there are already attempts to observe also QSOs fainter than L AGN 10 47 erg s −1 (see Willott et al 2007;Wang et al 2008Wang et al , 2010Omont et al 2013;Leipski et al 2013). The fraction of detected luminous QSOs with L AGN ≈ 3 × 10 47 erg s −1 turns out to be ≈ 30%, remarkably close to what is found at lower redshifts.…”
Section: Star Formation In Optically Selected Qsosmentioning
confidence: 99%
“…The first relevant piece of evidence is that the optically selected QSOs at z 2 exhibit on the average an M BH /M ⋆ mass ratio 3 − 20 times higher than the local value, Γ 0 ≈ 3 × 10 −3 , (e.g., McLure & Dunlop 2004;Peng et al 2006;Coppin et al 2008;Decarli et al 2010;Merloni et al 2010;Wang et al 2010;Targett et al 2012;Omont et al 2013;. The model envisages that such a finding is due to a selection bias.…”
Section: Stellar and The Bh Masses In Qsosmentioning
confidence: 99%
“…Dust and high-order molecular CO line emission in the host galaxies of the z∼6 quasars have been searched for using the Max Planck Millimeter Bolometer Array (MAMBO) on the IRAM-30m telescope (Bertoldi et al 2003a;Petric et al 2003;Wang et al 2007Wang et al , 2008Wang et al , 2011aOmont et al 2013), the Submillimeter Common User Bolometer Array (SCUBA) on the James Clerk Maxwell Telescope (Priddey et al 2003;Robson et al 2004;Priddey et al 2008), and the IRAM Plateau de Bure interferometer (PdBI, Bertoldi et al 2003b;Walter et al 2003;Carilli et al 2007;Wang et al 2010Wang et al , 2011a. The MAMBO survey of SDSS z∼6 quasars at 250 GHz (typical 1σ errors of 0.6 mJy) found that about 30% of them show strong continuum emission from dust at a temperature of 40 to 60 K, with FIR luminosities of a few 10 12 to 10 13 L ⊙ and inferred dust masses of a few 10 8 M ⊙ (Priddey & McMahon 2001;Bertoldi et al 2003a;Petric et al 2003;Wang et al 2011a).…”
Section: Introductionmentioning
confidence: 99%